Bystander Memory T Cells and IMiD/Checkpoint Therapy in Multiple Myeloma: A Dangerous Tango? - Anne Marit Sponaas (Frontiers in Immunology, 2021)
In this review article we discuss the role of the memory T cells in multiple myeloma (MM) and how they may influence immune responses in patients that received immunomodulating drugs and check point therapy.